Vital Lung Capacity in Active Smokers - Edy Sapada; Wita Asmalinda (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The prevalence of Indonesian smokers is increasing, the age of smokers is getting younger every day, and the number of cigarettes consumed is increasing. Smoking behavior or habits can have an impact on the emergence of pulmonary ventilation disorders due to irritation and excessive mucus secretion in the bronchi. The study aimed to determine the correlation between age, number of cigarettes, and duration of smoking with the vital capacity value of the lungs of active smokers. This type of research is analytic with a cross-sectional approach. This research was conducted for 30 days at the Ibnu Sina Clinic in Palembang. The sample of this study was active smokers who met the inclusion, and exclusion criteria. The number of samples is 50 respondents. Data analysis used the SPSS version 16 program. Sample characteristic data and measurement results were assessed using the Spearman test. The results of the study found there was a strong correlation between age variables in smoking duration and the vital lung capacity of the respondents. It was concluded that there was a significant correlation between the variables of age, number of cigarettes and duration of smoking with active smokers vital lung capacity values. It is suggested to conduct further research on cytokine variables Abstrak: Prevalensi perokok Indonesia makin meningkat, umur perokok tiap harinya semakin muda, dengan jumlah rokok yang dikonsumsi semakin banyak. Perilaku atau kebiasaan merokok dapat berdampak pada timbulnya gangguan ventilasi paru akibat iritasi dan sekresi mucus yang berlebihan pada bronkus Tujuan penelitian adalah untuk mengatahui korelasi antara umur, jumlah rokok dan lamanya mengkonsumsi rokok dengan nilai kapasitas vital paru perokok aktif. Jenis penelitian ini bersifat analitik dengan pendekatan cross sectional. Penelitian ini dilaksanakan selama 30 hari di Klinik Ibnu Sina Palembang. Sampel penelitian ini adalah perokok aktif yang memenuhi kriteria inklusi dan ekslusi. Jumlah sampel sebayak 50 responden. Analisis data mengunakan program SPSS versi 16. Data karakteristik sampel dan hasil pengukuran dinilai mengunakan uji spearman. Hasil penelitian didapatkan ada korelasi yang kuat antara variabel umur dan lama merokok dengan nilai kapasitas vital paru responden. Disimpulkan bahwa umur, jumlah rokok dan lama merokok berpengaruh terhadap nilai kapasitas vital paru perokok aktif. Disarankan untuk melakukan penelitian lebih lanjut pada variabel sitokin.